2017
DOI: 10.1002/ijgo.12343
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of shock index among women who did and did not receive blood transfusions due to postpartum hemorrhage

Abstract: Objective: To compare shock index (SI) values between women who required blood transfusion due to postpartum hemorrhage (PPH) and women who did not. Methods:In a case-control study, clinical data were assessed from the medical records of women requiring blood transfusion for PPH at a center in Brazil between 2012 and 2015 (n=105). A control group was randomly selected from women who did not receive blood transfusion (n=129). Conclusion:The SI might be useful to identify early vital sign changes due to PPH.Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…In the previous studies, the SI values above 0.9 in the postpartum period were related to blood loss above 1500 mL, UCI admission [18,19], and massive transfusion [17,18]. Statistically significant higher SI values were found in women that received blood transfusion due to PPH after vaginal delivery [15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the previous studies, the SI values above 0.9 in the postpartum period were related to blood loss above 1500 mL, UCI admission [18,19], and massive transfusion [17,18]. Statistically significant higher SI values were found in women that received blood transfusion due to PPH after vaginal delivery [15].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown the relationship between increased SI values and severe postpartum outcomes related to PPH [1520]. In the previous studies, the SI values above 0.9 in the postpartum period were related to blood loss above 1500 mL, UCI admission [18,19], and massive transfusion [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that SI values above 0.9 are associated with severe maternal outcomes due to PPH, including maternal death, ICU admission, blood transfusion of ≥4 blood units and invasive surgical interventions. (21,24) A previous study from our group showed that 30 minutes after delivery, the mean SI value found among women who received blood transfusion after vaginal delivery due to PPH was 0.88 ± 0.26 [22].…”
Section: Discussionmentioning
confidence: 98%
“…Clinicians emphasize a need for early warning criteria for PPH, which has a higher sensitivity to physiologic changes, ease of application in clinical practice, and prioritization of both the lost blood volume and its clinical outcomes, to indicate the severity of blood loss. 12 Shock index (SI), the ratio of HR divided by SBP, has been proposed as an early and reliable predictor of adverse outcomes in non-obstetric trauma and obstetric hemorrhage patients compared with conventional vital signs. 6 Clinical and experimental studies have shown that SI has an inverse linear correlation with left ventricular stroke work in acute circulatory failure.…”
Section: Introductionmentioning
confidence: 99%